THE DEVELOPMENT OF A TRIGONOMETRIC ENRICHMENT BOOK INTEGRATED WITH AUGMENTED REALITY - Meyta Fitrani, Lintang
Enrichment books are books that contain richer material and commonly used as a companion or complement to the main textbook. The use of technology in enrichment books can increase motivation in learning. Augmented reality is a technology that combines virtual objects and real objects. Trigonometry is one of some math topics that is considered difficult for most students to understand. The integration of augmented reality into the trigonometric enrichment book can make learning trigonometry easier and more interesting. This project aims to develop a trigonometric enrichment book integrated with augmented reality. This book was developed through four phases, namely the preparation phase, the design and product manufacturing phase, the implementation phase, and the evaluation phase. The book feasibility test method is carried out through a validation process and limited testing. Validation is carried out by experts consisting of one lecturer and one teacher. The validation instrument consists of five aspects of assessment, namely material aspects, augmented reality aspects, presentation aspects, language aspects and graphic aspects. The limited test was conducted on 23 students. The test instrument in the form of a response questionnaire is contained four aspects of assessment, namely aspects of interest, aspects of convenience, aspects of motivation, and aspects of innovation. The results of the validation show that the total mean value of validity is 3.52, which means that the book is included in the valid category according to the experts. The results of the limited test show that the total value of the total validity of enrichment books is 3.53, which means that the book is categorized as valid according to the students. Based on the results of validation and limited test, the augmented reality integrated trigonometric enrichment book is feasible to use.